In vitro antimicrobial activity of rosoxacin against Neisseria gonorrhoeae, Chlamydia trachomatis, and Ureaplasma urealyticum. - Dobson, R A (1980)
The antimicrobial activity of rosoxacin, a new quinoline antibacterial compound, was determined against the causative organisms of three sexually transmitted diseases. Rosoxacin demonstrated a high degree of activity against Neisseria gonorrhoeae clinical isolates, with the minimal inhibitory concentrations for 50% of these being 0.03 microgram/ml. The corresponding minimal inhibitory concentrations for penicillin, ampicillin, tetracycline, and spectinomycin were 0.25 U/ml, 0.125 microgram/ml, 0.25 microgram/ml, and 16 microgram/ml, respectively. Eleven strains of Chlamydia trachomatis were inhibited by 5 microgram of rosoxacin per ml, and each of seven Ureaplasma urealyticum strains was inhibited by 2 to 8 microgram of rosoxacin per ml. The results of these susceptibility studies, coupled with those of an earlier evaluation of the pharmacokinetics of rosoxacin, provide support for extending or undertaking clinical evaluations of this compound against infections with N. gonorrhoeae, C. trachomatis, and U. urealyticum.